Enrichment of pasta with faba bean does not impact glycemic or insulin response but can enhance satiety feeling and digestive comfort when dried at very high temperature. Issue 9 (2nd September 2015) - Greffeuille, Valérie; Marsset-Baglieri, Agnès; Molinari, Nicolas; Cassan, Denis; Sutra, Thibault; Avignon, Antoine; Micard, Valérie
<x xml:space="preserve">Abstract</x> High temperature drying strengthens the textural properties of legume pasta, reduces appetite and digestive discomfort and does not affect glycemic and insulin indices.